Relationship between academic self-efficacy and self-regulation of learning in students of the medical technology career - Luna Vargas, Sandro Antonio (2020)
The objective of this study was to determine whether there is a relationship between academic self-efficacy and self-regulation of learning in students of the medical technology career of the Private University of Tacna. The population consisted of all the students of the medical technology school of which only 92 decided to participate. The Inventory of Academic Self-Efficacy Expectations and the Self-Regulated Learning Inventory were used. Results: 57% academic self-efficacy feels safe, while in self-regulated learning the highest percentage is concentrated at an average level with 50%. Conclusion: when performing Spearman's correlation it was found that there is a positive and moderate correlation between self-efficacy academic and self-regulated learning in the students of the School of Medical Technology of the Private University of Tacna in 2018 (Rho de Spearman, 479 (p value 0.01)); By correlating academic self-efficacy with the dimensions of self-regulation of learning, the following conclusions were reached; academic self-efficacy with self-regulation of the executive strategy showed a positive and moderate correlation (sig. Bilateral 0.01 and correlation coefficient, 449), when related to self-regulation of cognition showed a positive and low correlation (sig. Bilateral 0.01 and correlation coefficient, 325), when relating it to self-regulation of motivation and affection, it showed a positive and low correlation (sig. Bilateral 0.01 and correlation coefficient, 398) and when relating it to self-regulation of the control of the environment, it showed a positive and low correlation (sig. Bilateral 0.01 and correlation coefficient, 385).